Reaction sintering of dense gadolinium-iron garnet (GdIG) material. Issue 10 (August 2021) - Stan, Magdalena; Lach, Radosław; Łańcucki, Łukasz; Rutkowski, Bogdan; Bućko, Mirosław M.
Abstract: Two synthesis methods of gadolinium-iron garnet (GdIG) materials were described. The first one was a typical co-precipitation-calcination method (CP method). In the second one gadolinium-iron perovskite (GdIP, GdFeO3) and iron oxide (α-Fe2O3) were mixed in proper amounts for GdIG stoichiometry (RS method). DSC data for precursor powder mixtures obtained from both synthesis routes allowed to examine heat effects. In the case of the CP method, two crucial reactions were observed. The first one at ab. 767 °C was associated with the formation of GdIP phase, whereas the second one at ab. 1080 °C was attributed to GdIG formation. For the RS method, only formation of GdIG at 1122 °C was observed. Both powder mixtures were sintered at 1200, 1300, and 1400 °C for 2 h. For the CP method, the highest density was below 90 % even at 1400 °C whereas for the RS method the density of materials sintered at the same temperature exceeded 97 %.